2013
DOI: 10.1530/eje-13-0433
|View full text |Cite
|
Sign up to set email alerts
|

Increased hypothalamic–pituitary–adrenal drive is associated with decreased appetite and hypoactivation of food-motivation neurocircuitry in anorexia nervosa

Abstract: Objective Corticotropin releasing hormone (CRH)-mediated hypercortisolemia has been demonstrated in anorexia nervosa (anorexia), a psychiatric disorder characterized by food restriction despite low body weight. While CRH is anorexigenic, downstream cortisol stimulates hunger. Using a food-related fMRI paradigm, we have demonstrated hypoactivation of brain regions involved in food motivation in women with anorexia, even after weight-recovery. The relationship between hypothalamic-pituitary-adrenal (HPA) axis dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 31 publications
(37 reference statements)
1
43
0
1
Order By: Relevance
“…Since cortisol concentrations were negatively associated with hunger and appetite ratings in all participants, these findings suggest that enhanced HPAA activity reflects malnutrition in untreated individuals with AN. Similar studies in patients [28][29][30][31]76] support this interpretation and a study in fasting healthy individuals suggests that these processes are generalizable to a non-clinical population [77]. Thus, we suggest that patients in the study by Monteleone et al [30] might have been malnourished to a larger extent than patients in our study, resulting in an enhanced HPAA response to the TSST.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Since cortisol concentrations were negatively associated with hunger and appetite ratings in all participants, these findings suggest that enhanced HPAA activity reflects malnutrition in untreated individuals with AN. Similar studies in patients [28][29][30][31]76] support this interpretation and a study in fasting healthy individuals suggests that these processes are generalizable to a non-clinical population [77]. Thus, we suggest that patients in the study by Monteleone et al [30] might have been malnourished to a larger extent than patients in our study, resulting in an enhanced HPAA response to the TSST.…”
Section: Discussionsupporting
confidence: 87%
“…A recent study, however, linked malnutrition and elevated HPAA reactivity. More specifically, while no differences in cortisol responses to a standardized mixed meal were found between healthy individuals and weight-recovered AN outpatients, patients with untreated AN showed significantly higher cortisol concentrations [76]. Since cortisol concentrations were negatively associated with hunger and appetite ratings in all participants, these findings suggest that enhanced HPAA activity reflects malnutrition in untreated individuals with AN.…”
Section: Discussionmentioning
confidence: 68%
“…16,24,45 Neurologic Malnutrition significantly affects the brain in children and adolescents because of the dynamic changes that are occurring in cognitive and structural braindevelopmentduringthisperiod. [87][88][89][90][91][92][93][94][95][96][97][98][99][100][101] Severely ill patients with AN have been shown to have reduced brain tissue volume and impaired neuropsychological functioning. 87 One study demonstrated persistent gray-white matter deficits and cerebrospinal fluid levels elevations on magnetic resonance imaging of weight restored patients with AN.…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…123,124 Finally, translational research is underway targeting known deficits in neurocognitive processes, neurotransmitters affected in EDs, and neuroanatomic changes found on imaging studies to tailor treatment and improve treatment response in patients with EDs. [88][89][90][91][92][93][94][95][96][97][98][99][100][101] Family-Based Treatment…”
Section: Treatment Modalitiesmentioning
confidence: 99%
“…Animal experiments have shown that food restriction increased adrenal gland weight and serum CORT levels after overnight fasting in rats (36), and enhanced HPA axis activity resulting in appetite loss and anorexia nervosa (39). Mixed results have been reported by studies assessing the effects of HFD exposure on CORT during developmental stages under basal conditions and after stress challenge (2,40).…”
Section: Discussionmentioning
confidence: 99%